THE EFFECT OF EARLY BREAST CANCER DETECTION EDUCATION WITH VIDEO ON WOMEN’S KNOWLEDGE OF RESTLESS AGE ABOUT BSE - Lola Aprillia; Enny Fitriahadi (Universitas Karya Husada Semarang, 2025)
Breast cancer is a condition where irregular breast cells proliferate uncontrollably and create tumors. The DIY Health Service conducts prompt identification of breast cancer every year through the Clinical Breast Examination program at least in Kulon Progo Regency 1.4%. The aim of the research was to assess the impact of video education on early breast cancer detection on the awareness of women of reproductive age regarding BSE. The approach utilized in the research was Cross Sectional, with a preliminary experiment research type utilizing a single group pre-test post-test research framework. The sampling technique used in this study was probability sampling with a nonparametric statistical test with the Wilcoxon match pair test technique. The results of the research on the early identification of breast cancer education with videos on the knowledge of women of childbearing age about BSE with a p-value of 0.000 <0.05. The conclusion in this study is that there is an influence and there is an increase before and after being given education about breast cancer with videos regarding the understanding of women of reproductive age about BSE at the Pengasih I Health Center Kulon Progo.